2017
DOI: 10.1373/jalm.2016.022467
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Fibroblast Growth Factor 23 in Human Plasma

Abstract: Background: Given the important emerging field of fibroblast growth factor 23 (FGF23) biology, there is a growing need for reliable data on FGF23 assay characteristics. We therefore evaluated the effects of different processing and storage conditions on FGF23 stability, as well as the assay precision of FGF23 measurements using 2 commercially available FGF23 ELISA kits. Methods: We measured plasma concentrations of intact FGF23 (iFGF23) and C-terminal FGF23 (cFGF23) in duplicate in 12 patients with a wide rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This confirmed two earlier studies that showed 23% reduction of FGF23 measured after a 8 h delay of centrifugation (compared with prompt centrifugation) using the second generation Immutopics assay [21]. Comparable reductions were found with the Millipore and Kainos assays [21,26]. With the DiaSorin assay no such decrease in FGF23 concentrations was found [27].…”
Section: Stability Of Fgf23supporting
confidence: 88%
“…This confirmed two earlier studies that showed 23% reduction of FGF23 measured after a 8 h delay of centrifugation (compared with prompt centrifugation) using the second generation Immutopics assay [21]. Comparable reductions were found with the Millipore and Kainos assays [21,26]. With the DiaSorin assay no such decrease in FGF23 concentrations was found [27].…”
Section: Stability Of Fgf23supporting
confidence: 88%
“…Reference change value (RCV) and index of individuality (II) (based on the CV I and CV G , without considering the CV A ) were calculated. RCV was calculated by the formula 2 1/2 × 1.96 × (CV A 2 + CV I 2 ) 1/2 with the assumption of two-tailed probability. We added the calculation of the lognormal RCV for decreases and lognormal RCV for increases according to Fokkema et al.…”
Section: Study Subjects and Methodsmentioning
confidence: 99%
“…Some significant papers have described preanalytics, analytical performance of available methods including iFGF23 and biological variation. 210 The biological variation of iFGF23 and cFGF23 can differ due to both biological (molecular distinctions, different half-lives) and analytical (different specificities of detection antibodies, different detection systems) factors. Data published previously have described the biological variation of cFGF23 or iFGF23 measured by ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…Interassay coefficients of variation for cFGF23 and iFGF23, determined from blinded replicate samples, were ,10%. We report additional performance characteristics for the cFGF23 and iFGF23 assays elsewhere (17).…”
Section: Exposures Measurements and Outcomesmentioning
confidence: 99%